2024
DOI: 10.3390/biom14010064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of De Novo Cholesterol Biosynthesis on the Initiation and Progression of Breast Cancer

Danila Coradini

Abstract: Cholesterol (CHOL) is a multifaceted lipid molecule. It is an essential structural component of cell membranes, where it cooperates in regulating the intracellular trafficking and signaling pathways. Additionally, it serves as a precursor for vital biomolecules, including steroid hormones, isoprenoids, vitamin D, and bile acids. Although CHOL is normally uptaken from the bloodstream, cells can synthesize it de novo in response to an increased requirement due to physiological tissue remodeling or abnormal proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 128 publications
0
1
0
Order By: Relevance
“…Cholesterol, a crucial element in the structure of cell membranes, plays a vital role in controlling intracellular traffic and signaling pathways. Though cells typically absorb cholesterol from the blood, they have the ability to produce cholesterol themselves when there is a greater demand caused by tissue remodeling or abnormal cell growth, such as in cases of cancer ( Coradini, 2024 ). It has been demonstrated that cholesterol biosynthesis is significantly enhanced in TNBC ( Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol, a crucial element in the structure of cell membranes, plays a vital role in controlling intracellular traffic and signaling pathways. Though cells typically absorb cholesterol from the blood, they have the ability to produce cholesterol themselves when there is a greater demand caused by tissue remodeling or abnormal cell growth, such as in cases of cancer ( Coradini, 2024 ). It has been demonstrated that cholesterol biosynthesis is significantly enhanced in TNBC ( Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%